Rational Design of MOF/COF Hybrid Materials for Photocatalytic H2 Evolution in the Presence of Sacrificial Electron Donors - Zhang, Feng‐Ming; Sheng, Jing‐Li; Yang, Zhao‐Di; Sun, Xiao‐Jun; Tang, Hong‐Liang; Lu, Meng; Dong, Hong; Shen, Feng‐Cui; Liu, Jiang; Lan, Ya‐Qian (Angewandte Chemie International Edition, 2018)
Crystalline and porous covalent organic frameworks (COFs) and metal‐organic frameworks (MOFs) materials have attracted enormous attention in the field of photocatalytic H2 evolution due to their long‐range order structures, large surface areas, outstanding visible light absorbance, and tunable band gaps. In this work, we successfully integrated two‐dimensional (2D) COF with stable MOF. By covalently anchoring NH2‐UiO‐66 onto the surface of TpPa‐1‐COF, a new type of MOF/COF hybrid materials with high surface area, porous framework, and high crystallinity was synthesized. The resulting hierarchical porous hybrid materials show efficient photocatalytic H2 evolution under visible light irradiation. Especially, NH2‐UiO‐66/TpPa‐1‐COF (4:6) exhibits the maximum photocatalytic H2 evolution rate of 23.41 mmol g−1 h−1 (with the TOF of 402.36 h−1), which is approximately 20 times higher than that of the parent TpPa‐1‐COF and the best performance photocatalyst for H2 evolution among various MOF‐ and COF‐based photocatalysts. Effective separation: A novel MOF/COF hybrid material assembled by covalent connecting two components, exhibits effective visible‐light‐driven photocatalytic H2 evolution due to the ideal band matching and effectively promoting the separation of the photogenerated charges and holes.